Water uses and risks in La Antigua watershed, Veracruz, Mexico - Román-Jiménez, Ana Rita; Mendoza-Briseño, Martín Alfonso; Velázquez-Martínez, Alejandro; Martínez-Ménez, Mario Roberto; Torres-Rojo, Juan Manuel; Ramírez-Maldonado, Hugo (Instituto de Ecología, A.C., 2016)
Water in Mexico is considered scarce resource. In this essay La Antigua watershed was chosen as a study case. In this site, watershed condition and land management policies were linked to water resource attributes suitable for different consumption uses. La Antigua watershed catches plenty of water; still people perceive problems. Evidence and analysis in this study uncovered a collective belief shared by the public, government, analysts and scientists in La Antigua. The belief sustains that water is vital, valuable and scarce. However, public behaviour contradicts such collective understanding. People choices are more consistent with a plentiful low cost resource, with no significant externalities. La Antigua scenario is not irrational, it represents the practical response towards only a fraction of all water stocks, a fraction which involves cultural processes redefining availability and good use of water moving through social systems. Understanding this scenario is essential to offering reliable insights in water policies to the decision makers in La Antigua, other parts of Mexico, and the world. Emphasizes that it is better to move away from technological solutions to deal with an imaginary scarcity, which is in fact unreal given a resource with so many and so different functions and valuations.